2020
DOI: 10.35849/bjare202001016
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Grain Quality of Some Improved Rice Varieties in Nigeria

Abstract: Field experiments were conducted between April and November 2016 at the Teaching and Research Farm of Ibrahim Badamasi Babangida University, Lapai (Latitude 09 0 02 " N and Longitude 06 0 34 " E) and Research Farm of College of Agriculture, Mokwa (Latitude 09 08''N and Longitude 05 0 04''E) to examine the effects of poultry manure time of application on the growth and yield of water melon varieties. The experiment was a 4 x 3 factorial laid in a Randomized Complete Block Design (RCBD) replicated three times. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Long-grain and extra-long-grain rice have intermediate to high amylose content which describes the Oje-igbale varieties. Results from Danbaba et al 16 showed the samples studied to be 6.69-5.44 mm, indicating long-grain to medium grain rice and were within the reported range.…”
Section: Medium Grain Rice Varieties Have Low To Intermediate Amylose...supporting
confidence: 55%
See 4 more Smart Citations
“…Long-grain and extra-long-grain rice have intermediate to high amylose content which describes the Oje-igbale varieties. Results from Danbaba et al 16 showed the samples studied to be 6.69-5.44 mm, indicating long-grain to medium grain rice and were within the reported range.…”
Section: Medium Grain Rice Varieties Have Low To Intermediate Amylose...supporting
confidence: 55%
“…Weight = Extra-heavy->25 g, heavy-20-25 g, moderately heavy <20 g, AA 1 -AA 3 (Adede-agidi rice variety from three different farmers) and OJ 1 -OJ 3 (Oje-igbale rice variety from three different farmers) differences exist in all the dimensions of the raw rice grain varieties. Cooked grains of medium-grain rice varieties are moist and tender and have a greater tendency to cling together than long grain rice and are desirable in making baby foods, whole cooked grains, breakfast cereals and risottos 16,17 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations